Physical Mechanical Properties of Biodegradable Plastics from Cassava Starch with Variation of Bagasse and Glycerol. - Triana Lindriati; Andrew Setiawan Rusdianto; Bustani Pakartiko; Firda Ainia Adha (Newinera Publisher, 2021)
Environmental problems are related to plastic waste that difficult to degrade naturally. Polysaccharides in the form of gelatinized cassava starch and bagasse containing 52.70% cellulose can replace commercial plastic polymers. This research was aimed to determine the effect of variations in bagasse and glycerol on physical, mechanical and biodegradation tests. The study used 2 factors CRD consisting of the addition of bagasse and glycerol. The results showed that the addition of bagasse and glycerol reducing the brightness with a value range of 44.82-76.15 and increased absorption between 2.61-10.64%. The thickness occurred between 0.79-1.11mm. The tensile strength values are 8.30-14.33 MPa, inversely proportional to the elongation value between 11.85-94.22%, but directly proportional to the modulus young value between 0.09-1.24 MPa. The highest biodegradation values were 0% bagasse and 40% glycerol. The three best treatments were found in the combination treatment of bagasse and glycerol 0% 20%, 0% 30%, and 0% 40%.